Do key audit matters impact financial reporting behavior?. Issue 2 (11th February 2020) - Gold, Anna; Heilmann, Melina; Pott, Christiane; Rematzki, Johanna
Abstract : This study experimentally examines whether the implementation of key audit matters (KAMs) in auditors' reports affects managers' reporting behavior. In line with prior research in psychology, we argue that greater transparency through KAMs leads to higher accountability pressure as managers may expect their judgments to be scrutinized more strongly in the presence of KAMs and, hence, to an improvement of financial reporting quality. Further, we examine whether informational precision (firm‐specific versus nonfirm‐specific information) in a KAM section moderates the effect of KAM presence on reporting behavior. Our findings show that managers' tendency to make an aggressive financial reporting decision is reduced in the presence of KAMs (compared to the absence of KAMs). This effect remains even when the description of the KAM is of low informational precision. Thus, our results suggest that KAMs serve as a beneficial mechanism for enhancing financial reporting quality by attenuating aggressive financial reporting behavior, regardless of the precision employed by auditors.